Political, process and programme failures in the Brexit fiasco: exploring the role of policy deception. Issue 5 (3rd May 2020) - Baines, Darrin; Brewer, Sharron; Kay, Adrian
ABSTRACT: We propose a conceptual framework of policy deception to help identify, analyse and explain Brexit as a policy fiasco. The framework casts light on the political use of the device of an in/out European Union (EU) referendum by David Cameron. The paper develops the argument that the referendum did not offer a binary choice between two policy options for the United Kingdom's (UK) relationship with the EU representing different, but commensurable preferences, because one option was 'baseless' in that it was unfounded in any policy analysis. The label of policy deception usefully reveals that many of the political, process and programme failures at the heart of the Brexit fiasco have their roots in the referendum. We conclude that the concept of policy deception contributes usefully to emerging work on why the Brexit policy fiasco occurred, and is likely to be a fruitful topic for future work. Abstract :